Vocabulary Size of University of Aden English Language Students - Abdulnaser Mohammed Ali Naqeeb (REiLA)
This research paper tried to evaluate the department of English students' vocabulary size by using Nation Vocabulary size tests (VST). The study used a sample of the third level students at the department of English-Faculty of Education-Aden at the University of Aden in three categories according to their academic achievement in the class (High =80-100, Medium= 70-79.99 and Low =less than 69.99). To measure the vocabulary size, the researcher used on Nation and Beglar (2007) (14000) vocabulary size test. Based on the analysis of students correct answers in the VST, the study found that students' vocabulary size ranges between 1000-8000 words with variant percentages. It was found that (80%) of third level students vocabulary size (high 08-100 and medium 70-79.99) is in the range (1000-3000), (76%) of third level students vocabulary size (high 08-100) is in the range (1000-5000) and (51%) are in the range (1000-8000). The study found that (59%) of third level students (medium 70-79.99) are in the range (1000-5000) and (40%) of them are in the range (1000-8000). The third level students (low, less than 69.99) recorded the lowest size by (50%) in the range (1000-3000), (41%) in the range (1000-5000) and only (21%) are in the range (1000-8000). Considering the total word size of the three categories together, the study found that (70%) are in the range (1000-3000), (59%) range in the range (1000-5000) and (37%) are in the range (1000-8000).